Stability of branonium - Ellison, J; Lukas, A (2004)
We analyze the orbital motion of a light anti-D6-brane in the presence of a stack of heavy, distant D6-branes in ten dimensions, taking account of possible time variations in the background moduli fields. The Coulomb-like central potential arising through brane-antibrane interactions is then modified to include time-dependent prefactors, which generally preclude the existence of stable elliptical orbits.